Regulation of activities in protected areas - Püschel Hoeneisen, Lorna (Revista de Derecho Ambiental, 2019)
The present article aims to reflect on the regulation of productive activities in protected areas. After an introduction on the subject, the legislation of three countries that are a reference in biodiversity conservation is presented, to then examine the current regulation in Chile. Based on the foregoing, some regulatory options are raised and recommendations are made on how to legally address the regulation of activities in protected areas.